The American Board of Obstetrics and Gynecology's remote certifying examination: successes and challenges - Pooja Shivraj, MS, PhD; Rajat Chadha, PhD; Deana Dynis, EdD; Kirk Diepenbrock, MS; Barbara L. Hoffman, MD; Susan Ramin, MD; George D. Wendel, Jr., MD (Elsevier, 2022)
In response to the COVID-19 pandemic, the American Board of Obstetrics and Gynecology canceled the 2020 in-person subspecialty certifying examinations and developed remote administration of 4 subspecialty certifying examinations in 2021 for both examiners and candidates. Because of the continued risks of the COVID-19 pandemic, the 2021 specialty certifying examinations and the 2022 subspecialty certifying examinations were also administered remotely for candidates. For these examinations, examiners participated remotely in 2021 and were at the American Board of Obstetrics and Gynecology testing center in 2022. Overall, the American Board of Obstetrics and Gynecology remote certifying examinations have been well-received by candidates and examiners according to posttest survey data. Candidate performance has been comparable to that observed in the previous in-person examinations. In this review, we describe our implementation, process modifications, successes, and challenges with remote testing. During this process, the American Board of Medical Specialties approval was required, and the Standards for Educational and Psychological Testing served as our testing-industry guideline to ensure valid interpretation of scores and fairness to candidates.